For a posthuman ethics: Contributions from Braidotti, Sloterdijk and Marchesini - Piedra Alegría, Jonathan (2023)
In this article, we explore the concept of a posthuman ethics through the contributions of three prominent thinkers: Rosi Braidotti, Peter Sloterdijk, and Roberto Marchesini. Posthumanism is a theoretical and philosophical framework that challenges the limitations of classical humanism and rethinks the human being's position in relation to nature, technology, and other forms of alterity. This perspective transcends the anthropocentrism and Cartesian dualism that have dominated Western thought, promoting instead a relational understanding of the human. Here, interactions and connections with the environment, technological systems, and other living beings are crucial for the construction of human identity and experience. Through an analysis of the works of Braidotti, Sloterdijk, and Marchesini, the article proposes a posthuman ethics that integrates elements from these three perspectives to address the ethical, social, and ecological challenges of our time.